MENINGKATKAN KEDISIPLINAN BELAJAR SISWA MELALUI KONSELING BEHAVIORISTIK DENGAN TEKNIK SHAPING - Elina Septi Rahayu; Richma Hidayati; Susilo Rahardjo (Jurnal Muria Research Guidance and Counseling (MRGC), 2022)
The purpose of this study is to describe the factors that cause low student discipline in learning at MTs Sabilul Ulum Mayong and to help students improve discipline in learning through behavioristic counseling with shaping techniques. The type of research used is case study research. The data analysis used is inductive qualitative data analysis which consists of data reduction, data presentation, and drawing conclusions. The results showed that there was an increase in student discipline in learning at MTs Sabilul Ulum Mayong after being given behavioristic counseling services with shaping techniques. This can be seen from the behavior of the two counselees who start to go to school on time, collect assignments on time, and pay attention to the teacher during lessons. Thus, it can be concluded that the discipline in learning of MTs Sabilul Ulum Mayong students can be improved through behavioristic counseling with shaping techniques.